2021
DOI: 10.6023/cjoc202103044
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites and Bioactivities of Penicillium sp. Sourced from Mangrove from 2007 to 2020

Abstract: Mangrove plants grow in tropical and subtropical intertidal zones with acid, salt and oxygen deficit. The particularity of the growth environment provides a special host environment for mangrove fungi. The unique genetic background and metabolic pathway of mangrove-derived fungi make their secondary metabolites have novel structures and diverse biological activities. The genus of Penicillium is widely distributed, which is a large group of mangrove-derived fungi. It can produce metabolites with various structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…In summary, 23 secondary metabolites, including six new isocoumarin derivative talaromarins A-F (1-6) and 17 known analogues (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) were obtained from the mangrovederived fungus Talaromyces flavus TGGP35. Compounds 6-11, 17-19 and 22 exerted similar or better antioxidant activity than the positive control trolox (IC 50 = 0.29 mM), with IC 50 values ranging from 0.009 to 0.27 mM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, 23 secondary metabolites, including six new isocoumarin derivative talaromarins A-F (1-6) and 17 known analogues (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) were obtained from the mangrovederived fungus Talaromyces flavus TGGP35. Compounds 6-11, 17-19 and 22 exerted similar or better antioxidant activity than the positive control trolox (IC 50 = 0.29 mM), with IC 50 values ranging from 0.009 to 0.27 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, more than 1400 new secondary metabolites produced by mangrove-derived fungi have been reported, including polyketides, alkaloids, terpenes and so on, and more than 40% of secondary metabolites displayed cytotoxic, antibacterial and insecticidal activities etc. [3][4][5][6][7][8]. Among them, isocoumarins are lactone-type derivatives derived from the polyketide pathway [9,10], and they possess a wide range of pharmacological activities such as antibacterial 7-hydroxyoospolactone and parapholactone [11], anti-inflammatory (±)-prunomarin A [12], cytotoxic lunatinin [13], insecticidal peniciisocoumarins A and B, antiplasmodial monocerin [14], antioxidant and α-glucosidase inhibitory penicimarin N [15], brine shrimp (Artemia salina) lethal and broad-spectrum antimicrobial penicimarins G-K [16,17], penicoffrazins B and C [18].…”
Section: Introductionmentioning
confidence: 99%
“…One review has summarised the chemical diversity and bioactivity of NPs reported from mangrove-derived Penicillium species and another discusses the antimicrobial NPs reported from mangrove fungal epiphytes. 329,330 Analysis of MarinLit data 2 shows that there have been 294 papers reporting new MNPs from mangrove fungi since 2014 but only 92 report fungi isolated from roots or sediment. These root and sediment studies report fungi associated with 21 species of plant of which ve are coastal or salt marsh species, not mangroves (Table 1).…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
“…One review has summarised the chemical diversity and bioactivity of NPs reported from mangrove-derived Penicillium species and another discusses the antimicrobial NPs reported from mangrove fungal epiphytes. 329,330…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…The environment of the mangrove system harbors unique traits, for instance, high salinity, low oxygen, tidal gradients, high temperature, and excessively intense light, resulting in an active ecosystem with various microorganisms [ 1 , 2 , 3 , 4 , 5 ]. Mangrove-associated microorganisms have been demonstrated to be a reliable source of bioactive metabolites and have likewise drawn the attention of NP researchers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. A large number of structurally unusual and bioactive NPs have been discovered from the mangrove-associated microorganisms, including fungal and bacterial endophytes isolated from the mangrove plants’ leaves, branches, and roots [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%